MINORITAS MUSLIM DI ASIA TENGGARA ABAD KE-20: ANALISIS KOMPARATIF SINGAPURA, FILIPINA, DAN THAILAND DALAM PERSPEKTIF STUDI PENDIDIKAN SEJARAH - Nazaruddin; Dwi Fitri; Martunis; Novi Quintena Rahayu; Ade Irma Gemilau (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The 20th century was a crucial period in Southeast Asian history, marked by political transformation, colonialism, and the formation of nation-states that significantly impacted the position of Muslims as a minority group in Singapore, the Philippines, and Thailand. This study aims to comparatively analyze the historical, social, political, and educational dynamics of Muslim minorities in these three countries from the perspective of historical education studies. This study uses a qualitative method with a historical-comparative approach, utilizing secondary data in the form of history books, scientific journals, colonial archives, and relevant state policy documents. The research findings show that Islam in all three regions initially developed peacefully through trade, da'wah, and social relations, but experienced a shift in position due to colonialism and modern state policies. Singapore represents a model of state accommodation towards Muslim minorities through multicultural policies and the strengthening of religious institutions, the Philippines demonstrates historical marginalization that has triggered a prolonged conflict with the Moro community, while Thailand demonstrates identity pressure through national assimilation policies. The findings of this research confirm that the historical experiences of Muslim minorities are contextual and heavily influenced by state ideology and power relations. The implications of this research for history education are the importance of presenting minority narratives in an inclusive and comparative manner to foster multicultural awareness, tolerance, and critical thinking skills in students regarding the relationship between religion, state, and identity in Southeast Asia.